2019
DOI: 10.1177/1687814019871431
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the aircraft bay/landing gear coupling noise at low subsonic speeds and its suppression using leading-edge chevron spoiler

Abstract: When the aircraft opens the bay door to let the landing gear either drop or retract, the incoming flow will result in a significant amount of coupling noise from the bay and the landing gear. Here, an experimental study was reported to characterise the acoustic performance and flow field at low subsonic speeds. Also, we examined a passive control method leading-edge chevron spoiler to suppress the noise. The experiment was performed in a low-speed aeroacoustic wind, the bay was simplified as a rectangular cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…An additional way to obtain a similar noise reduction is by adding small, locally mounted solid/perforated fairings [17,18], meshes [19][20][21] or hub caps [22][23][24][25] to landing gear in order to improve the local aerodynamic shape or reduce local velocities, as well as some more advanced concepts such as; optimised bay door design [26], wheel bay treatments [23,27,28] and an upstream solid, retractable flow deflector [29][30][31]. A full review of noise reduction technologies for aircraft landing gear can be found in Zhao et al [32] and a review of bio-inspired aerodynamic noise control in Wang et al [33].…”
Section: A Air Curtain Technology and Permeable Flow Fairingsmentioning
confidence: 99%
“…An additional way to obtain a similar noise reduction is by adding small, locally mounted solid/perforated fairings [17,18], meshes [19][20][21] or hub caps [22][23][24][25] to landing gear in order to improve the local aerodynamic shape or reduce local velocities, as well as some more advanced concepts such as; optimised bay door design [26], wheel bay treatments [23,27,28] and an upstream solid, retractable flow deflector [29][30][31]. A full review of noise reduction technologies for aircraft landing gear can be found in Zhao et al [32] and a review of bio-inspired aerodynamic noise control in Wang et al [33].…”
Section: A Air Curtain Technology and Permeable Flow Fairingsmentioning
confidence: 99%